The Strategic Relationship between Health Status, Total Health Expenditure and Economic Growth in Jordan - al-hamouri, Qasem; Al-BALAS, Bayan (International Journal of Psychosocial Rehabilitation, 2020)
improvement in health is considered as much important as country's income improvement, no way to separate between them especially when thinking about achieving development and human welfare. Health status is measured by several key indicators, this study utilized three indicators that include infant mortality rate (IMR), crude death rate (CDR), and under-five mortality (u5m). This research paper aims to examine the relationship between the health status, the health care expenditure and the economic growth through the period 1995-2013. Research objectives Due to the great emphasis of health role on economic growth and its significance, this study has been designed and implemented within the Hashemite Kingdom of Jordan to investigate and explore a research model that determines the relationship between the health–health expenditure and economic growth To achieve the first goal, the ARDL approach was utilized to estimate a logarithmic form of the traditional production function where output was a function of health expenditure, capital and labor and foreign aid. According to the results of the estimated elasticities of the output with respect to health expenditure, capital, labor and foreign aid were 0.21, 0.125,042; -0,011 respectively. The results identified a positive impact of health expenditure on economic growth which indicates the importance and necessity to develop and recommend a comprehensive strategic plan for the health sector. The results also revealed a positive impact of both gross domestic product and Per capita health expenditure on health indicators.